Lactuca racemosa Willd., Source of Antioxidants with Diverse Chemical Structures - Klaudia Michalska; Danuta Jantas; Janusz Malarz; Klaudia Jakubowska; Wojciech Paul; Anna Stojakowska (Molecules)
Ethanolic extracts from the roots and aerial parts of the hitherto chemically uninvestigated lettuce species Lactuca racemosa Willd. (Cichorieae, Asteraceae) were chromatographically separated to obtain eight sesquiterpenoids, two apocarotenoids (loliolide and (6S,9S) roseoside), and three phenolic glucosides (apigenin 7-O-glucoside, eugenyl-4-O-β-glucopyranoside, and 5-methoxyeugenyl-4-O-β-glucopyranoside). Four of the isolated sesquiterpene lactones (8-α-angeloyloxyleucodin, matricarin, 15-deoxylactucin, and deacetylmatricarin 8-β-glucopyranoside) have not previously been found either in Lactuca spp. or in Cicerbita spp. In addition, HPLC-PAD chromatographic methods were used to estimate the deacetylmatricarin derivatives, luteolin 7-O-glucoside, and caffeic acid derivatives contents in the analyzed plant material. The aerial parts contained c. 3.0% dry weight of chicoric acid and equal amounts (0.4%) of caftaric acid and luteolin 7-O-glucoside. The roots contained fewer phenolic metabolites but were rich in deacetylmatricarin glucoside (c. 1.3%). The aglycone of the most abundant sesquiterpene lactone was evaluated with respect to its neuroprotective effect in H2O2- and 6-OHDA-treated human neuroblastoma SH-SY5Y cells. This compound, at concentrations of 10 and 50 μM, provided partial protection of undifferentiated cells, and at a concentration of 50 μM, it provided partial protection of retinoic acid-differentiated cells from H2O2-induced damage. In a model of 6-OHDA-evoked cytotoxicity, the sesquiterpenoid was less effective. Our findings may support the inclusion of this plant into the human diet.